Models of initiation fatigue crack paths proposed by Macha (Fracture and Structural Integrity, 2015)
Professor E. Macha devoted his academic life to solving the problems connected with randommultiaxial fatigue in components of machines and structures. In his studies he formulated stress, strain andenergy criteria related to critical plane concept. He also proposed several methods to determine critical planeposition. In particular, he formulated and verified weight functions applied in order to determine critical planeposition. The variance method constituted another significant contribution to the development of methods fordetermining critical plane position. Apart from these criteria, Macha was exploring energy approach in fatigue ofmaterials and the development of fatigue cracks.He has also observed that strain characteristics multiplied by stress amplitude determined at specimen half-lifeare applied to estimate fatigue life using energy criteria. However, for cyclically instable materials, stressamplitude value may differ a lot; therefore he proposed the method to determine energy fatigue characteristicsdirectly from experimental research.